Aspernolides F and G, new butyrolactones from the endophytic fungus Aspergillus terreus. (December 2015) - Ibrahim, Sabrin R.M.; Elkhayat, Ehab S.; Mohamed, Gamal A.; Khedr, Amgad I.M.; Fouad, Mostafa A.; Kotb, Mohamed H.R.; Ross, Samir A.
Graphical abstract: Highlights: The CHCl3 fraction of the endophytic fungus Aspergillus terreus was investigated. Two new butyrolactones and six known compounds were isolated. Their structures were established by various spectroscopic analyses. The anti-microbial, anti-malarial, anti-leishmanial, and cytotoxic activities of the compounds were evaluated. Abstract: Two new butyrolactones: aspernolides F (6 ) and G (7 ), together with three stigmasterol derivatives: (22 E, 24 R )-stigmasta-5, 7, 22-trien-3-β-ol (1 ), stigmast-4-ene-3-one (2 ), and stigmasta-4, 6, 8(14), 22-tetraen-3-one (3 ), two meroterpenoids: terretonin A (4 ) and terretonin (5 ), and a butyrolactone derivative: butyrolactone VI (8 ) have been isolated from the endophytic fungus Aspergillus terreus isolated from the roots of Carthamus lanatus (Asteraceae). Their structures were determined by spectroscopic means (1D, 2D NMR, and HRESIMS), as well as optical rotation measurement and comparison with literature data. The isolated compounds were evaluated for their anti-microbial, anti-malarial, anti-leishmanial, and cytotoxic activities. Compound1 displayed a potent activity against MRSA and C. neoformans with IC50 values of 0.96 μg/mL and 4.38 μg/mL, respectively compared to ciprofloxacin (IC50 0.07 μg/mL) and amphotericin B (IC50 0.34 μg/mL), respectively. While, 6 showed good activity against C. neoformans (IC50 5.19 μg/mL) and mild activity against MRSA (IC50 6.39 μg/mL). Moreover, 1 and2 exhibited very good anti-leishmanial activity towards L. donovani with IC50 values of 4.61 and 6.31 μg/mL, respectively and IC90 values of 6.02 and 16.71 μg/mL, respectively.